Use of essential oils extracted from the Caatinga as an alternative for the treatment of infectious diseases and inflammation - de Sousa, Bárbara Mendes; Torres , Anna Clara Silva; Guedes, Pedro Henrique Alves; Silva , Liz Helena Pereira; de Lira , Thais Freitas; Matias, Teresa Dávila Cruz; Bezerra , Cicero Igno Guedes; Figueirêdo, Maria Adriana Simão; Sá, Lucas de Oliveira; Alves, Sabrina Kaylane da Silva; Sampaio , Mariana Gomes Vidal (Seven Editora, 2024)
Secondary plant metabolites, such as essential oils from the Caatinga, have diverse therapeutic properties, including antimicrobial and anti-inflammatory action. Studies highlight its effectiveness against infections, promoting alternative use in medicine. The research addressed in this work provides a comprehensive view of the therapeutic potential of essential oils extracted from medicinal plants found in the Caatinga Morphoclimatic Domain, located in Northeast Brazil. Thus, this is a systematic review of the qualitative literature, based on descriptors that follow the direction of the Health Sciences Descriptors (DeCS), used in the VHL (Virtual Health Library) search engine: "Caatinga", "Medicinal Plants", "Volatile Oils", "Anti-inflammatory", "Antibacterial", "Antiparasitic" and "Antioxidant", which were applied in the following databases: Scielo; Medline; Lilacs; PubMed and Elsevier. Several plant species and their respective essential oils were investigated, highlighting their antioxidant, antimicrobial, anti-inflammatory and antiparasitic properties. The results showed that the essential oils of Caatinga plants have a wide range of chemical compounds, such as terpenes, aldehydes, phenols and esters, which confer their medicinal properties. These compounds have the potential to be used as therapeutic alternatives in the treatment of various health conditions, including bacterial, parasitic and inflammatory infections. In addition, the study highlights the importance of preserving the biodiversity of the Caatinga and the traditional knowledge associated with the use of medicinal plants in the region. The integration between popular knowledge and scientific research is essential to fully explore the therapeutic potential of these plants, contributing to the promotion of public health and the development of new therapies. In addition, it is essential to ensure sustainable practices for the use and management of medicinal plants in the Caatinga, to preserve their biodiversity and the ancestral knowledge associated with their use. DOI:https://doi.org/10.56238/sevened2024.016-007